Arabidopsis thaliana eIF4E1 and eIF(iso)4E Participate in Cold Response and Promote Translation of Some Stress-Related mRNAs - Salazar-Díaz, Kenia; Aquino-Luna, Mayra; Hernández-Lucero, Eloísa; Nieto-Rivera, Brenda; Pulido-Torres, Marlon A.; Jorge-Pérez, Jesús H.; Gavilanes-Ruiz, Marina; Dinkova, Tzvetanka D. (Frontiers in Plant Science, 2021)
Plant defense and adaptation to adverse environmental conditions rely on gene expression control, including mRNA transcription, processing, stability and translation. Sudden temperature changes are common in the era of global warming, thus, understanding plant acclimation responses at the molecular level become imperative. mRNA translation initiation regulation has a pivotal role in achieving the synthesis of the appropriate battery of proteins needed to cope with temperature stress. Here we analyzed the role of translation initiation factors belonging to the eIF4E family in Arabidopsis acclimation to cold temperatures and freezing tolerance. Using knockout and overexpressing mutants of AteIF4E1 or AteIF(iso)4E we found that AteIF4E1, but not AteIF(iso)4E overexpressing lines displayed enhanced tolerance to freezing without previous acclimation at 4 ºC. However, knockout mutant lines, eif(iso)4e-1 and eif4e1-KO, were more sensitive to the stress. Cold acclimation in wild type plants was accompanied by increased levels of eIF4E1 and eIF(iso)4E transcript levels, polysomes enrichment, and shifts of these factors from translationally non-active to active fractions. Transcripts, previously found as candidates for eIF(iso)4E or eIF4E1 selective translation changed their distribution in both, polysomes and total RNA in the presence of cold. Some of these transcripts changed their polysomal distribution in the mutant and in one eIF4E1 overexpressing line. According to this, we propose a role of eIF4E1 and eIF(iso)4E in cold acclimation and freezing tolerance by regulating the expression of stress-related genes.